Delivery of cesarean section tends to reduce umbilical zinc levels in healthy newborns - Priyantini, Sri; Soemantri, -; Widyastiti, Nyoman Suci (International Journal of Human and Health Sciences (IJHHS), 2020)
Background: Indonesia is estimated to be among countries with deficiencies in zinc intake. Zinc deficiency increase the risk of immune deficiency, preterm birth, retarded fetal growth, duration of infection healing, and stunting. Umbilical cord zinc levels can reflect zinc levels of newborns. Research on newborn zinc in Indonesia is still limited. Objective: Look for factors related to zinc levels of the newborns umbilical cord. The factors studied included maternal/newborn characteristics, and mode of delivery. Methods: A Cross sectional study of 88 healthy newborns at term pregnancy with their healthy mothers. Zinc samples were taken from cord blood immediately after birth. Measurement of zinc levels with Atomic Absorption Spectrophotometer. Chi-Square test was used to prove the relationship between low zinc levels (< 65μ/dl) with characteristics of both mother and newborn. The Mann-Whitney test was used to prove differences in zinc levels between groups according to characteristics, mode of delivery, and birth weight. Software SPSSstatistic 21. Results: There was no significant relationship between mother and newborn characteristics with low umbilical cord zinc levels (<65μg/dl), with a p value > 0.05. There was a significant difference in mean umbilical cord zinc levels between the two groups (p=0.015), that cesarean section delivery had a mean rank of lower zinc levels (41.5μg/ dl) median 79.8 (min.50.9-max.140.3 μg/dl) compared to spontaneous vaginal delivery (59.3μg/dl) median 97.7 (min.57.6-max.132.9μg/dl). Umbilical cord zinc levels from 2500 - < 2800 g birth weight group have lower mean rank (37.7μg/dl) compared to 2800 - 3900 g birth weight group (48.2μg/dl), with a p value = 0.028. Conclusions: There is a tendency to decrease zinc levels in healthy newborns from cesarean delivery. Decreased zinc levels in healthy newborns may cause lower birth weight. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 298-304